The Principle of Legal Certainty in the Statute of Kotor (1616, Venice) - Janko Paunović (Journal on European History of Law)
The paper explores the principle of legal certainty in the medieval commune of Kotor, focusing on the distribution of power and judicial authority. It examines the legal structure of Kotor, including appeal mechanisms and the role of notaries, primarily from the Italian Peninsula, in shaping the local legal system. Additionally, it highlights the codification process of Kotor’s statutes, first published in Venice in 1616, and the influence of Venetian governance. The author analyses the balance of power between local aristocracy and external oversight by Venice, showcasing how aristocratic control was maintained, particularly in judicial and administrative matters, while safeguarding legal certainty.